Dissolved Organic Carbon Reduces Uranium Bioavailability and Toxicity. 1. Characterization of an quatic Fulvic Acid and Its Complexation with Uranium[VI] - Trenfield, M.; McDonald, Suzanne; Kovacs, K.; Lesher, E.; Pringle, J.; Markich, S.; Ng, J.; Noller, B.; Brown, P.; Van Dam, R. (American Chemical Society, 2011)
Fulvic acid (FA) from a tropical Australian billabong (lagoon) was isolated with XAD-8 resin and characterized using size exclusion chromatography, solid state cross-polarization magic angle pinning, 13C nuclear magnetic resonance spectroscopy, elemental analysis, and potentiometric acid-base fitration. Physicochemical characteristics of the billabong FA were comparable with those of the Suwannee River Fulvic Acid (SRFA) standard. The greater negative charge density of the billabong FA suggested it contained protons that were more weakly bound than those of SRFA, with the potential for billabong water to complex less metal contaminants, such as uranium (U). This may subsequently influence the toxicity of metal contaminants to resident freshwater organisms. The complexation of U with dissolved organic carbon (DOC) (10 mg L-1) in billabong water was calculated using the HARPHRQgeochemical speciation model and also measured using flow field-flow fractionation combined with inductively coupled plasma mass-spectroscopy. Agreement between both methods was very good (within 4% as U-DOC). The results suggest that in billabong water at pH 6.0, containing an average DOC of 10 mg L-1 and a U concentration of 90 g L-1, around 10% of U is complexed with DOC.